Pengaruh Kecukupan Pakan Terhadap Produksi Susu dan Kualitas Susu Kambing Di Kecamatan Turi Kabupaten Sleman Yogyakarta - Dian Novita Sari; Ajat Sudrajat; Niken Astuti; Raden Febrianto Christi (Fakultas Pertanian Universitas Majalengka, 2024)
This research aims to determined the effect of feed adequacy on the production and quality of dairy goat milk in Turi District. This research was carried out in the field and laboratory from 01 to 24 October 2023. A total of 98 dairy goat breeders were selected as respondents with the criteria of having at least 1 year of farming experience and having at least 2 animals. From each goat they raise, milk samples are taken to test the quality in the laboratory. The data obtained were analyzed descriptively and by multiple linear regression analysis. The results showed that the average age of farmers is 44 years, with an education level of 86% high school graduates, the number of family dependents of 4-5 people is 67%, the majority work as farmers 52% (69% ≤10 years and 31% ≥11 years). Livestock ownership status is 100% privately owned with an average ownership of 2-5 heads. The average body weight of dairy goats was 40.13 ± 6.91 kg, with milk production of 2.21 ± 0.51 liters/day. Furthermore, the milk quality variable shows that the average specific gravity and non-fat solids are 1.055 ± 0.08 and 8.42 ± 0.43. Feed adequacy (Dry Matter) is 1.43 and Crude Protein adequacy is 7.44. Milk production was significantly (p<0.05) 52.6% influenced by the level of feed adequacy with the regression equation Y = -1.513 + 0.033XI + 0.495X2. Meanwhile, milk density was 48.5% influenced by the level of feed adequacy (p>0.05) with the regression equation Y = 1.043 + 0.073XI - 0.013X2. Likewise, the lean solitaire variable which was not significant (p>0.05) was influenced by the level of feed adequacy (0.75%) with the regression equation Y = 6.874 + 0.155XI + 0.183X2. It was concluded that the adequacy of feed for dairy goats in Turi District for production was sufficient and for milk quality it was in accordance with the 2011 SNI.